Fatores condicionantes na formação de aglomerados no turismo :um estudo da perspectiva dos empresários em região do litoral do Nordeste do Brasil - Rodrigues Júnior, Giovani (2006)
The tourism has been presented as an alternative of production for determined regions of the Country. In this scene, one perceives that it is necessary to observe where each locality is situated in order to face an highly competitive and globalized world. The data used on this work was collected on a field research with the entrepreneurs of the coast of the City of Parnamirim/RN. The main objective of this research was to analyze the conditioning factors in the formation of clusters on tourism, according to the perception of the entrepreneurs of the Association of the Entrepreneurs of the Coast of Parnamirim AELP, based on the competitive advantages showed on Porter s model, referring to the conditions of the production factors, the demand, the associated and support sector, the strategy and structure of the company. On the statistical treatment, descriptive analysis and crossed analysis were carried through. According to the data, the research suggests the existence of some determinative factors that can generate competitive advantages, that whwn integrated, can congregate attributes that allow the formation of a competitive tourist accumulation in a region of the northeast coast of Brazil. The research also evidenced that the entrepreneurs have a strong dependence of the governmental actions